1984
DOI: 10.1203/00006450-198407000-00019
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Neonatal Pig As a Model for Infant Nutrition: Effects of Different Proportions of Casein and Whey Protein in Milk on Nitrogen Metabolism and Composition of Digesta in the Stomach

Abstract: Summarygiven formulas containing predominantly whey proteins did Abbreviation DM, dry matterSimilarities in the digestive system of man and the pig suggest that results of studies on digestion and nutrition in the pig may be applicable to man (9). Some similarities in neonatal glucose metabolism have also been demonstrated (1 3). Other studies in neonatal pigs have assumed that results may be relevant, for example, in studies on protein nutrition (28, 23). However, no systematic comparisons of protein utiliza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

1985
1985
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…Casein and a-protein were more completely hydrolysed and the digesta left the stomach faster than raw or heated soya bean. A series of studies with 28-d-old piglets killed 1 h after feeding showed that the appearance of trichloroacetic acid (TCA)-soluble N in gastric contents was slower for bovine milk proteins than for fish proteins (Newport, 1979), isolated soya-bean protein (Newport, 1980) or a whey-supplemented milk (Newport & Henschel, 1984); heat-damaged milk proteins were less rapidly digested than undamaged proteins (Braude et al 1971).…”
Section: Digestion P R O T E I N Smentioning
confidence: 99%
See 1 more Smart Citation
“…Casein and a-protein were more completely hydrolysed and the digesta left the stomach faster than raw or heated soya bean. A series of studies with 28-d-old piglets killed 1 h after feeding showed that the appearance of trichloroacetic acid (TCA)-soluble N in gastric contents was slower for bovine milk proteins than for fish proteins (Newport, 1979), isolated soya-bean protein (Newport, 1980) or a whey-supplemented milk (Newport & Henschel, 1984); heat-damaged milk proteins were less rapidly digested than undamaged proteins (Braude et al 1971).…”
Section: Digestion P R O T E I N Smentioning
confidence: 99%
“…Further evidence of the complexity of emptying of milk or casein-based diets is shown by the more rapid emptying of human milk than of infant formulas in infants (Cavell, 1981); this may be related in part to the amounts of whey protein as a percentage of total protein in bovine (20), porcine (50) and human (80) milks. Thus, Newport & Henschel (1984) found that the gastric emptying rate of protein was highest for diets with a high whey:casein ratio. The nature of the curd formed in the stomach after consumption of bovine milk is also related to the rates of gastric emptying; soft curds from UHT-treated or cultured milk emptied faster than the hard curds formed from raw or pasteurized milk in the studies by Meisel & Hagemeister (1984).…”
Section: Proteins and Amino Acidsmentioning
confidence: 99%
“…The hypomotility of the premature infant allows for stasis resulting in prolonged interaction of gastrointestinal flora with enteral feeds as well as prolonged contact of the mucosa with potentially injurious byproducts of this interaction. Brush border enzymes beta-galactosidase (lactase) and alpha-glucosidases (sucrase, isomaltase, maltase, and glucoamylase) reach functional maturity at different gestational stages with lactase maturing the last between 30–34 weeks [ 43 , 44 ]. As the premature infant bowel is exposed to lactose-containing cow’s milk-based formula, the limited ability of the neonate’s small bowel to digest lactose provides the proximal colonic flora extra substrate to ferment.…”
Section: Discussionmentioning
confidence: 99%
“…The BUN values measured during PN are comparable to preterm infants receiving primarily parenteral nutrition during the first week after delivery [ 48 ]. The low and sometimes undetectable BUN levels for preterm pigs fed the low protein formulas are comparable to those of term pigs fed low protein formulas [ 49 ] and preterm infants fed a low protein formula that still promotes growth [ 50 ]. The low BUN values suggest that the majority of the protein was partitioned into accretion of lean body mass, with little catabolism of dietary or tissue protein along with lower energetic costs for nitrogen disposal.…”
Section: Discussionmentioning
confidence: 99%